Efficiency and accuracy of the domain and functional decomposition strategies for the wave-structure interaction problem. (15th December 2022) - Aliyar, Sithik; Ducrozet, Guillaume; Bouscasse, Benjamin; Sriram, V.; Ferrant, Pierre
Abstract: Extreme waves can be modelled in a numerical wave tank (NWT) as a focusing wave in order to generate events that are crucial for designing any offshore structures. The focused wave generation implemented in the completely nonlinear potential solver Higher Order Spectral method (HOS-NWT) with the time-reversal technique was used in the present work. The OpenFOAM based solvers foamStar and foamStarSWENSE which use the domain decomposition and the functional decomposition approach, respectively, were used to couple with a HOS-NWT to perform the focusing wave interaction with the structure (in this case, a cylinder). The incident waves from HOS-NWT are blended into a foamStar and foamStarSWENSE subdomain, where the waves will propagate and interact with the structure within their domain. In the SWENSE methodology, the total field in the computational domain is divided into the incident field and a complementary field. foamStar solves for the total flow fields, and foamStarSWENSE solves for the complementary (total minus incident) flow fields. The Volume of Fluid (VoF) method was selected to capture the interface. 2D parametric studies for focused wave generation were carried out with both solvers, and 3D wave interactions for different mesh types (coarse, medium, and fine) were investigated to understand the convergence for such transient type problems. For verification, the case's uncertainty was quantified using the Richardson extrapolation approach, and validation was then done by comparing the results to the experiment. The computational efficiency of the two coupling techniques was also compared, and recommendations for solver improvements are made. In general, when solving the problem of wave generation and propagation in 2D and 3D conditions, foamStarSWENSE surpassed foamStar in accuracy. On the other hand, when the simulation included a structure in the domain, the accuracy of the solution in foamStar and foamStarSWENSE was nearly the same, but the foamStar performed better in terms of computational cost. Overall, both coupling approaches generate a realistic depiction of focused wave interaction and force over the cylinder at a minimum computational cost. Highlights: Domain and functional decomposition coupling procedures are compared and validated Grid convergence is studied through Richardson extrapolation and cross-correlation Both foamStar and foamStarSWENSE are accurate, even with the coarsest mesh. With a similar setup foamStarSWENSE seems more accurate, but is more costly